PERAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA INDRA MEMBERIKAN PELAYANAN DALAM PENYEDIAAN AIR BERSIH DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Rizki Aswandi; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in Indragiri Hulu. Indragiri Hulu District Government through the Regent's decision No. 17 of 2008 has established the Regional Water Company with the goal of providing clean water for people, especially in the District Rengat Indragiri Hulu. It is to know the role of the Regional Water Company (PDAM) to provide services in water supply in the district Rengat Indragiri Hulu, this research using qualitative methods. Data collection techniques in this study were interviews and tracking documentation. PDAM as a drinking water service facilities have a strategic role in the effort to accelerate the improvement of public health degree Kab.Indragiri Hulu .. In this study determined that as many as 9 people informant Director of PDAM Tirta Indra, Head of Section subscriptions, and while the Head of Account Creator customer care of and has been assigned to take care of 6 people each perform data collection and documentation obtained depth interviews with informants. Based on the research that the provision of clean water in Sub Rengat particular, but in exercising their ministry there are several inhibiting factors, such as lack of budget to cope with the scale of the damage or kebocoraan pipe, the shortage of personnel in the field, lack of repair tools, human resources employees who do not fit and specialized training in the field of customer service that are not implemented, the PDAM Tirta For Indra should build a good management information systems and monitoring systems and integrated services sisitem and implement standards of service. Thus the government Indragiri Hulu should be an evaluation of the management of PDAM Tirta Indra. According Ratminto (2010: 24), the public service must have a standard of service that is a measure of providing services. The standard of the services include: set settling time from the time of application until the completion of the service, including complaints, namely the service fee rate services including the details set out in the service delivery process, service product that is the result of service that will be accepted in accordance with the conditions set, standardized procedures for service providers and service recipients, including complaints, facilities and infrastructureinclude the provision of adequate services and infrastructure by public service providers, and personnel competence service providers should be set appropriately based on the knowledge, expertise, skills, attitudes, and behavior . Keywords: taps, Clean Water Services, Indragiri Hulu